PERJANJIAN PRANIKAH: SOLUSI BAGI WANITA - Ahmad Dahlan (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
prenuptial agreement (Perjanjian pranikah) is social phenomenon that still uncommon among Indonesian society. However,polygamy practice that still controversial necessitates such an arrangement and prenuptial agreement can become basic to alleviatepolygamy that not based on Islamic law. prenuptial agreement content not only cover polygamy, but also harta gono gini (joint marriageproperty) arrangement, even touched family life design that will practiced by spouse.